Land Use Change caused by Demographic Change? Evidences and Conclusions - Hoffmann, Jens; Dehne, Peter; Weith, Thomas; Strauß, Christian; Gaasch M.A., Nadin (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Demographic change is often mentioned as one main driver for land use change. Since the 1970s, experts of spatial planning discuss consequences of demographic change. Currently, the topic is of importance in societal debates, too. However, does demographic change really directly influence land use change? As yet, comprehensive models of land use change are missing that describe the consequences of demographic change on land use in par- ticular; mainly partial models exist up to now. Thus, this paper contributes to the questions if there is any empirical evidence for direct relations between demographic change and land use change and what consequences this has for spatial research and spatial development policies. For an- swering these questions, we conducted a comprehensive literature analysis for the period from 2005 to 2013 with regard to the German discourse and discussed the results at two expert workshops. The analysis shows a lack of refer- ences that provide evidence for a direct influence of demo- graphic change on land use. This is in particular significant for the following types of land use: agriculture, forestry, tourism, and nature protection. Also indirect cause effect relations cannot be proved fully due to the lack of empiri- cism. Consequently, serious uncertainties exist regarding the effectiveness of spatial planning and spatial develop- ment approaches within this context.
Keywords: Demographic change; Land use; Land use change; Land management